EFFECTIVENESS OF KECOMBRANG FLOWER (ETLINGERA ELATIOR) AS A LARVACIDE FOR AEDES AEGYPTI INSTAR III MOSQUITOES - Destriani, Ni Putu Ita; Risma, .; Pasaribu, Irma A.; Rohmah, Etik A. (E-Jurnal Medika Udayana; Vol 13 No 2 (2024): E-Jurnal Medika Udayana, 2024)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus infection where the vector is the female Aedes aegypti mosquito. DHF causes high mortality and morbidity because a vaccine for DHF has not yet been found. DHF therapy is still supportive and symptomatic, causing this disease to remain a health problem for the community. The purpose of this study was to determine the effectiveness of kecombrang flower ( Etlingera elatior ) as Aedes aegypti instar III larvicide. This research was conducted at the Institute of Tropical Disease (ITD) Universitas Airlangga in July 2023. The research design used was true experimental design with post-test only group control design . Divided into 7 groups, namely negative control, 0.1%, 0.6%, 1.1%, 1.6%, 2.1% and 2.6%. The number of samples used in the study was 560 larvae. Each group contained 20 larvae with 50ml of solution containing kecombrang flower extract. Repetition was done 4 times at each concentration. The test used was Kruskal-Wallis (p<0.05), Post-Hoc Mann Whitney U test (p<0.05). The results showed the highest average larval mortality at concentrations of 2.1% and 2.6% at 100% and the lowest average at a concentration of 0.1% at 28.75%. In the Kruskal-Wallis test , each treatment group showed significant differences (p<0.05). The Mann Whitney U post hoc test showed significant differences between the two treatment groups.   Keywords : Aedes aegypti , Kecombrang flower ( Etlingera elatior ), Larvacide